Add-value of Lactarius deliciosus and Macrolepiota procera wild mushrooms due to their nutritional and nutraceutical potential - Fernandes, Ângela (2012)
This study describes the nutritional and nutraceutical potential of two species of wild edible mushrooms (Lactarius deliciosus and Macrolepiota procera) commonly consumed in the region of Trás-os-Montes, Northeast Portugal. The nutritional parameters analyzed were moisture, ash, fat, proteins, carbohydrates and energetic contribution. Free sugars and fatty acids were also determined by high performance liquid chromatography coupled with a refractive index detector (HPLC/RI) and gas chromatography coupled with a flame ionization detector (GC/FID), respectively. Macronutrient profile revealed that the studied species are rich sources of carbohydrates, proteins and energy, revealing low fat content. Mannitol and trehalose were the most abundant sugars in both species. The main fatty acid found in M. procera was linoleic acid, while stearic acid was the most abundant in L. deliciosus. The nutraceutical potential was also evaluated through antioxidant properties measured by DPPH (1,1-diphenyl-2-picrylhydrazyl) radical scavenging activity, reducing power, inhibition of β-carotene bleaching and inhibition of LPO using thiobarbituric acid reactive substances (TBARS). The mentioned assays showed and high antioxidant activity for both samples species. Phenolic acids and related compounds were analysed by HPLC coupled to diode array detection (HPLC/DAD) and p-Hydroxybenzoic acid was found in L. deliciosus and cinnamic acid in M. procera.